Review article: Let us talk about snakebite management: A discussion on many levels. (17th June 2019) - Turner, Damian; Winter, Suzanne; Winkel, Kenneth; MacIsaac, Christopher; Padula, Andrew; Braitberg, George
Abstract: We want to discuss antivenom use in snakebite clinical practice guidelines. Coronial reviews in Victoria of two cases of snakebite envenomation, one described in detail below, prompted us to submit this paper for a wider audience and debate. Venom and antivenom levels were measured in the case detailed below, but not in the other. The coroner received conflicting and varied advice from experts regarding the dose of antivenom. The Victorian Department of Health and Human Services and the Australasian College for Emergency Medicine were instructed to review snakebite management guidelines, particularly with respect to antivenom dosage. The discussion that took place among medical experts led to considerable media attention. We discuss the potential fallout when there is no consensus among medical experts.